Pola makan dan obesitas sebagai faktor risiko diabetes mellitus tipe 2 di Rumah Sakit Sanglah Denpasar - Ni Komang Wiardani; Hamam Hadi; Emy Huriyati (Jurnal Gizi Klinik Indonesia, 2007)
Background: Diabetes Mellitus (DM) is a chronic disease with its increasing prevalence worldwide, including in Indonesia and in Bali province especially among adult group. The increasing prevalence of DM is followed by the increasing prevalence of obesity affected by changes in lifestyle and unhealthy dietary patterns.Objective: The study was conducted to investigate relations between dietary patterns and obesity with type 2 DM in Sanglah Hospital, Denpasar.Method: The study was observational analytic with matched case control study. Subject of the study was divided into two groups, i.e. case and control with comparison case and control 1:2 which matched to age and sex. The cases were type 2 DM patients who had recently diagnosed on first visited in Sanglah Hospital. Control 1 was outpatients of non-type 2 DM in Sanglah Hospital and control 2 were taken from the case-neighboring household. Total subject were 147, taken by consecutive method. Collected data were subject identity, dietary patterns, physical activity, weight, height, waist circumference and fasting blood sugar. Dietary patterns were collected using Food Frequency Questionnaire (FFQ), physical activity was collected using modified International Physical Activity Questionnaire (IPAQ), and fasting blood sugar were estimated using biosensor of glucose. Multiple logistic regression models were used to identify risk factors associated with type 2 DM.Result: This study showed that there were 5 variables significantly related with type 2 DM, i.e. interaction of overall obesity with the dietary fiber intake (OR:10.7; 95% CI: 3.5-33.7), family history (OR:5.5, 95% CI: 2.2-13.3), source of high fat animal protein (OR:4.9, 95% CI:1.5-16.1), source of low fat animal protein (OR:0.1, 95% CI: 0-0.5), hypertension (OR:3.7, 95% CI:1.4-9.9)Conclusion: The interaction between overall obesity with dietary fiber intake, family history, source of high fat animal protein, source of low fat animal protein and hypertension were the risk factors of type 2 DM occurrence in Sanglah Hospital, Denpasar.